2016
DOI: 10.18632/oncotarget.10485
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a circulating MicroRNA signature to distinguish recurrence in breast cancer patients

Abstract: There is an urgent need for novel noninvasive prognostic biomarkers for monitoring the recurrence of breast cancer. The purpose of this study is to identify circulating microRNAs that can predict breast cancer recurrence. We conducted a microRNA profiling experiment in serum samples from 48 breast cancer patients using Exiqon miRCURY microRNA RT-PCR panels. Significantly differentiated miRNAs for recurrence in the discovery profiling were further validated in an independent set of sera from 20 patients with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 53 publications
(56 reference statements)
3
64
0
1
Order By: Relevance
“…Similar results were also observed in other clinical breast cancer cohorts where miR-205-5p expression levels were measured by qRT-PCR [25, 26] and by in situ hybridization [27]. In addition to the miR-205-5p downregulation in high grade tissue biopsies, the presence of blood circulating miR-205-5p, indicating an overall high expression correlated with tumor chemo sensitivity and higher rates of disease free survival [28]. …”
Section: Discussionsupporting
confidence: 80%
“…Similar results were also observed in other clinical breast cancer cohorts where miR-205-5p expression levels were measured by qRT-PCR [25, 26] and by in situ hybridization [27]. In addition to the miR-205-5p downregulation in high grade tissue biopsies, the presence of blood circulating miR-205-5p, indicating an overall high expression correlated with tumor chemo sensitivity and higher rates of disease free survival [28]. …”
Section: Discussionsupporting
confidence: 80%
“…Upregulation of miR-21-5p has been associated with breast cancer pathogenesis, invasion, and metastasis. [4450] Additionally, miR-21 overexpression has been found to promote breast cancer proliferation in vitro . [51] Upon examination of 344 primary breast cancer patients, Qian et al reported that high miR-21 expression was associated with features of aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Four miRNAs were upregulated (miR-21-5p, miR-375, miR-205-5p, and miR-194-5p) and three miRNAs were downregulated (miR-382-5p, miR-376c-3p, and miR-411-5p). 130 …”
Section: Circulating Mirnasmentioning
confidence: 99%